FREEZING CHARACTERISTICS OF TROPICAL FISHES - SHENOY, A VASANTH; PILLA!, V K (Fishery Technology, 2025)
The influence of different prefreezing ice storage periods on the biochemical and organoleptic qualities of Indian oil sardines (Sardi. nella !ongiceps) in the individual quick frozen (IQF) and block frozen (BF) forms and frozen storage at temperatures of-12°C and-23°C was studied. The shelf-Hfe of the sardines varied between 24 and 2 weeks for samples iced for 0 to 5 days prior to freezing. The deterioration in quality was accompanied by considerable increase in the peroxide value (PV) and free fatty acid (FFA) content and decrease in saJt extractability of the proteins. These changes were more rapid at-12°C than at-23°C. BF sardines appeared to be better than IQF samples with respect to the biochemical changes although the differences in overall organoleptic quality were not significant.